Status and influencing factors of work stress among nurse managers in western China: a cross-sectional survey study - Zhuoxin Yang; Huaping Huang; Guirong Li (BMC, 2024)
Abstract Aims Due to the nature of their work, nurses are more prone to experiencing psychological consequences than other healthcare workers. However, evidence on the emotional burden of nurse managers in China is limited. Furthermore, perceived organizational support has been approved that can affect mental health outcomes. Therefore, this study aimed to investigate the status quo and influencing factors of nurse managers' work stress, and their possible relationship with perceived organizational support, which could further provide more countermeasures to safeguard their health. Methods A cross-sectional online survey of 21 secondary and tertiary hospitals was conducted in a city in Sichuan province, Southwest China, using a convenience sampling method between October and November 2022. Data were collected using the general information questionnaire, the Chinese version of the Stress Overload Scale (SOS) and the perceived Organizational Support Scale (POSS). SPSS 23.0 was applied to analyze the data. Results In total, 380 participants completed the survey. The median scores (interquartile range [IQR]) for SOS and POSS were 60.50 (50.00, 70.75) and 51.00 (44.00, 55.00), respectively. The work stress of the nurse managers was negatively correlated with perceived organizational support (P < 0.01). Multiple linear regression analysis showed that age older than 40 years, from secondary hospitals, working in emergency or pediatric wards, and professional qualification of supervisor nurse or deputy supervisor nurse, and the scores of POSS less than 51 significantly influenced the work stress of the nurse managers. Conclusions Our study shows that nurse managers are more prone to work stress, and organizational support can effectively reduce this stress. Governments and hospital administrators should pay more attention to providing comprehensive strategies based on various risk factors to protect and promote psychological health.